Developing an Information System Design Kopma Unisba - Azhar Fauzan; Magnaz Lestira Oktaroza (UNISBA Press, 2022)
Abstract. The Student Cooperative of the Islamic University of Bandung is an organization that is a legal entity as well as a Student Activity Institute (LKM). Kopma Unisba itself is included in the type of consumption cooperative. The problems faced by Kopma Unisba are related to the inadequate division of tasks, inadequate documents and procedures used. The purpose of this research is to create an information system design model that is suitable for Kopma Unisba and especially in the finance department and business units such as kopmart, photocopying, and general trading. The existence of a computerized system can help cooperatives to be more effective and efficient in their work and can store and process data regularly. The method used in this design is FAST (Freamwork For Application Of System Technique), and follows the System Development stage, and uses JAD (Joint Application Development) data collection techniques so that it will produce a more structured system. The result of the design is to design an information system for business units such as sales, purchases, and inventory that can support operational activities at Kopma Unisba. Abstrak. Koperasi Mahasiswa Universitas Islam Bandung merupakan organisasi yang berbadan hukum sekaligus merupakan Lembaga Kegiatan Mahasiswa (LKM). Kopma Unisba sendiri termasuk dalam jenis koperasi konsumsi. Permasalahan yang dihadapi oleh Kopma Unisba yaitu berkaitan dengan kurang sesuainya pembagian tugas, dokumen dan prosedur yang digunakan kurang memadai.Tujuan penelitian adalah untuk membuat model perancangan sistem informasi yang sesuai pada Kopma Unisba dan terkhusus pada bagian keuangan dan unit usaha seperti kopmart, fotocopy, dan perdagangan umum. Dengan adanya sistem yang terkomputerisasi dapat membantu koperasi agar lebih efektif dan efisien dalam bekerja serta dapat menyimpan dan mengolah data secara teratur. Metode yang digunakan dalam perancangan ini adalah FAST (Freamwork For Application Of System Technique), dan mengikuti tahapan System Development, serta menggunakan teknik pengumpulan data JAD (Joint Application Development) sehingga, akan menghasilkan sistem yang lebih berstruktur. Hasil perancangan yang dilakukan, yaitu membuat rancangan sistem informasi pada unit usaha seperti bagian penjualan, pagian pembelian, dan bagian persediaan yang dapat menunjang kegiatan operasional pada Kopma Unisba.